2010
DOI: 10.1002/mrd.21224
|View full text |Cite
|
Sign up to set email alerts
|

Directional differentiation of chicken primordial germ cells into adipocytes, neuron-like cells, and osteoblasts

Abstract: Primordial germ cells (PGCs) are useful for producing transgenic chickens and preserving genetic material in avian species. In this study, we investigated the in vitro differentiation potential of chicken PGCs into different cell types. For differentiation into adipocytes, chicken PGCs were cultured for 21 days in induction media containing dexamethasone, insulin and/or 3-isobutyl-1-methylxanthine (IBMX), and differentiation rates ranging from 74% to 91% were identified by oil red-O and alkaline phosphatase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…These findings match previous reports; Li et al [35] established that chicken PGCs could be directionally differentiated into adipose, neuronlike cells and osteoblasts. Jung et al [16] reported successful transfer of both chicken adult GSCs and embryonic GGCs to embryo and adult chicken hosts, whereas Trefil et al [21,36] restored spermatogenesis in sterilized roosters by transplantation of dispersed testicular cells from chicken adult donors.…”
Section: Xenotransfer Of Avian Spermatogonial Stem Cellssupporting
confidence: 94%
“…These findings match previous reports; Li et al [35] established that chicken PGCs could be directionally differentiated into adipose, neuronlike cells and osteoblasts. Jung et al [16] reported successful transfer of both chicken adult GSCs and embryonic GGCs to embryo and adult chicken hosts, whereas Trefil et al [21,36] restored spermatogenesis in sterilized roosters by transplantation of dispersed testicular cells from chicken adult donors.…”
Section: Xenotransfer Of Avian Spermatogonial Stem Cellssupporting
confidence: 94%
“…The induction medium was 90% DMEM, 10% FBS, 5.5 × 10 −5 M β-ME, 1 × 10 −7 M retinoic acid (RA), and 5 × 10 −4 M 3-isobutyl-1-methylxanthine (IBMX) [ 50 , 68 , 69 ]. The induced SSCs were stained with toluidine blue and NSE.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the above procedures about using media A and media B were repeated three times. The induction medium B maintained the cultured cells for the duration of the experiment, when they were stained with Oil red O [ 24 , 68 ]. At this time, expression of the adipocyte-specific gene peroxisome proliferator-activated receptor-γ ( PPAR-γ ) and C/EBPα was detected by qRT-PCR [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…PGCs were isolated from the gonads of 5.5‐day‐old embryos, and SSCs were isolated from the testis of 18‐day‐old chicks. PGCs and SSCs were separated by performing equilibrium density gradient centrifugation and differential adhesion . PGC colonies were identified using a mouse anti‐chicken C‐kit antibody (dilution, 1:50; Santa Cruz Biotechnology, Santa Cruz, CA) and fluorescein isothiocyanate (FITC)‐conjugated goat‐anti‐mouse IgM (anti‐fluorescein isothiocyanate) as the second antibody (dilution, 1:50; Santa Cruz Biotechnology), according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%